The Wellbeing of the Haematology Workforce in the UK - Stewart-Lord A; Appiah B; Das Neves Eusebio C; Wright J; Pavord S; Leary A (Journal of Multidisciplinary Healthcare)
Adele Stewart-Lord,1 Bernice Appiah,1 Cidalia Das Neves Eusebio,1 Josh Wright,2 Sue Pavord,3 Alison Leary1 1Institute of Health and Social Care, London South Bank University, London, UK; 2Haematology Department, Sheffield Teaching Hospitals NHS Foundation Trust, Northern General Hospital, Sheffield, UK; 3Clinical Haematology, Oxford University Hospitals NHS Foundation Trust, John Radcliffe Hospital, Oxford, UKCorrespondence: Adele Stewart-Lord, Institute of Health and Social Care, London South Bank University, 103 Borough Road, London, SE1 0AA, UK, Tel +44 20 7815 7931, Email stewara2@lsbu.ac.ukPurpose: Globally, haematology is recognised as a highly specialised field of practice that deals with the diagnosis, treatment, and management of blood disorders. To meet the demand of increased service delivery, the workforce needs to be able to adapt and respond to challenges. Specialists and organisations require specific intelligence to understand their workforce, the demand for labour, and plan for the future. This study aimed to understand wellbeing among the haematology workforce across the multidisciplinary team.Methods: A mixed methods explanatory sequential design was used to collect data on wellbeing. Stage 1 online questionnaire was distributed through membership networks. Descriptive statistics were used to analyse the data. Stage 2, data were collected through online semi-structured interviews and analysed thematically. Ethical approval was gained through University Ethics Panel.Results: Haematology professionals face multiple stressors due to exposure of emotive situations. This study found high levels of burnout and frustration, with professionals saying that, they were exhausted after each shift. The increasing demands of the haematology service contribute to the overall pressure experienced by staff, making them feel overwhelmed. Inadequate staffing was a defining challenge in providing adequate service delivery, meeting patients’ needs whilst attempting to maintain wellbeing. Working hours /schedule and on-call for many participants reflected their efforts to meet the changing demands within services.Conclusion: This is the first study to focus exclusively on a range of healthcare professionals within haematology. The diverse and demanding nature of work, as well as the complexities of managing haematology patients, emphasised the need for a high level of expertise, adaptability, and resilience within the workforce. Supportive work environments are needed to allow professionals to establish and uphold personal boundaries and disengage with work to ensure a sustainable work–life balance.Keywords: haematology, workforce, wellbeing, workload, staffing